The Tetracyanopyridinide Dimer Dianion, σ‐[TCNPy]22−. Issue 35 (28th July 2016) - Hao, Jingjun; Rheingold, Arnold L.; Kavand, Marzieh; van Schooten, Kipp J.; Boehme, Christoph; Capdevila‐Cortada, Marçal; Novoa, Juan J.; Wöss, Eva; Knör, Günther; Miller, Joel S.
Abstract: The reaction of 2, 3, 5, 6‐tetracyanopyridine (TCNPy) and Cr(C6 H6 )2 forms diamagnetic σ‐[TCNPy]2 2− possessing a 1.572(3) Å intrafragment sp 3 –sp 3 bond. This is in contrast to the structurally related 1, 2, 4, 5‐tetracyanobenzene and 1, 2, 4, 5‐tetracyanopyrazine that form π‐dimer dianions possessing long, multicenter bonds. Abstract : Do or dimer : The reaction of 2, 3, 5, 6‐tetracyanopyridine (TCNPy) and Cr(C6 H6 )2 forms diamagnetic σ‐[TCNPy]2 2− possessing a 1.572(3) Å intrafragment sp 3 –sp 3 bond. This is in contrast to the structurally related 1, 2, 4, 5‐tetracyanobenzene and 1, 2, 4, 5‐tetracyanopyrazine that form π‐dimer dianions possessing long, multicenter bonds.